Efektivitas Dakwah dalam Media Digital untuk Generasi Z - Efendi, Erwan; Ramadhani, Gita; Tanti, Tria (Institut Agama Islam Nasional Laa Roiba Bogor, 2024)
Da'wah is currently carried out through digital media. Advances in technology and informatics provide a new wind for the spread of da'wah. The development of digital media coincided with the birth of Generation Z. This article uses a descriptive approach as a writing method. Based on literature analysis and experience, the focus of this research is to analyze and explain how da'wah through digital media has succeeded in reaching generation Z people. Generation Z, who are accustomed to digital technology, need a da'wah approach that suits their preferences and habits. Therefore, this research aims to reveal how effective da'wah in digital media is for generation Z. This study uses a writing method through a descriptive approach. The results of the analysis show that da'wah content that is adapted to the lifestyle and needs of generation Z, and presented in familiar and interesting language, tends to be more effective. Apart from that, direct interaction and interaction with the audience on social media and other digital platforms also plays an important role in increasing the effectiveness of da'wah. However, there are challenges in maintaining the attention of generation Z who are exposed to a variety of digital content. Therefore, creativity in preaching and the use of interactive features of digital media are important keys in increasing the effectiveness of preaching. This research provides important insights for preachers and parties involved in digital da'wah to understand more effective strategies in reaching generation Z. By optimizing the use of digital media, da'wah becomes more relevant and its impact can be felt more widely by generation Z in facing challenges and changing times.